Lactobacillus plantarum BSGP201683 Isolated from Giant Panda Feces Attenuated Inflammation and Improved Gut Microflora in Mice Challenged with Enterotoxigenic Escherichia coli - Liu, Qian; Ni, Xueqin; Wang, Qiang; Peng, Zhirong; Niu, Lili; Wang, Hengsong; Zhou, Yi; Sun, Hao; Pan, Kangcheng; Jing, Bo; Zeng, Dong (Frontiers in Microbiology, 2017)
In this work, we searched for an effective probiotic that can help control intestinal infection, particularly enterotoxigenic Escherichia coli K88 (ETEC) invasion, in giant panda (Ailuropoda melanoleuca). As a potential probiotic strain, Lactobacillus plantarum BSGP201683 (L. plantarum G83) was isolated from the feces of giant panda and proven beneficial in vitro. This study was aimed to evaluate the protective effect of L. plantarum G83 in mice challenged with ETEC. The mice were orally administered with 0.2 mL of PBS containing L. plantarum G83 at 0 colony-forming units (cfu) mL−1 (control; negative control, ETEC group), 5.0×108 cfu mL−1 (LDLP), 5.0×109 cfu mL−1 (MDLP), and 5.0×1010 cfu mL−1 (HDLP) for 14 consecutive days. At day 15, the mice (LDLP, MDLP, HDLP, and ETEC groups) were challenged with ETEC and assessed at 0, 24, and 144 h. Animal health status; chemical and biological intestinal barriers; and body weight were measured. Results showed that L. plantarum G83 supplementation protected the mouse gut mainly by attenuating inflammation and improving the gut microflora. Most indices significantly changed at 24 h after challenge compared to those at 0 and 144 h. All treatment groups showed inhibited plasma diamine oxidase activity and D-lactate concentration. Tight-junction protein expression was down-regulated, and interleukin (IL)-1β, IL-6, IL-8, TLR4, and MyD88 levels were up-regulated in the jejunum in the LDLP and MDLP groups. The number of the Enterobacteriaceae family and the heat-labile enterotoxin (LT) gene decreased (P < 0.05) in the colons in the LDLP and MDLP groups. All data indicated that L. plantarum G83 could attenuate acute intestinal inflammation caused by ETEC infection, and the low and intermediate doses were superior to the high dose. These findings suggested that L. plantarum G83 may serve as a protective probiotic for intestinal disease and merits further investigation.